POTENTIAL OF AGRITOURISM IN KARNATAKA - Vanishree C T; Honnalli, S.H. (International Journal of Psychosocial Rehabilitation, 2020)
India has always been conscious of the need for decades to diversify the economic base of the country. While agritourism has been around the world in one form or another, extensive academic research has not been conducted in this area. This research breaks new ground in that it focuses solely on the potential of agritourism in Karnataka, a tourist destination preferred in India. The objectives of this research are to know the potential for agritourism in Karnataka by understanding the basic geographical, economic, political and related data about it, identify factors which inhibit farmers from linking their produce with the tourism industry and the factors inhibiting hospitality industry on relying on local farmers for generating revenue through agritourism so that the true potential for agritourism could be ascertained.